New Spectrophotometric Methods for the Assay of Etoricoxib - Purneshwar, Polavarapu Bhargavi (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Etoricoxib is an anti-inflammatory drug. New derivative spectrophotometric methods have been developed for the assay of Etoricoxib in tablets. Materials and Methods: The present study was performed in three different reagents - sodium acetate buffer, hydrochloric acid, and phosphate buffer using Shimadzu double beam ultraviolet (UV)-VIS spectrophotometer UV-1800 model. Results and Discussion: Etoricoxib has obeyed Beer–Lambert’s law in all the three reagents, and the methods were validated. Conclusions: The methods are economical and used for the assay of Etoricoxib in pharmaceutical dosage forms.